Factors Associated with the Symptom of Depression among Elderly in Indonesian Urban Areas - haerawati Idris; Shania Nursiah Hasri (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Depression is the most common mental disorder among the elderly, affecting approximately 7% of the global elderly population (WHO, 2017). This study aims to analyze factors influencing symptoms of depression among the elderly in urban areas of Indonesia. Adopting a quantitative cross-sectional design, the researchers scrutinized secondary data available publicly from Indonesian Basic Health Research (Riskesdas) 2018. The data were analyzed using logistic regression statistics. We found that there are 11.2% (n=3200) of respondents who experienced symptoms of depression from 28.570 elderly in Indonesia urban areas. The bivariate results showed that gender (95% CI 1.257-1.536), history of chronic diseases (95% CI 1.834-2.242), educational status (95% CI 3.033-5.141), employment status (95% CI 1.434-1.770), marriage status (95% CI 1.134-1.391), and physical activity (95% CI 1.255-1.565) significantly correlated with the symptoms of depression among elderly. Low educational status is the most dominant variable influencing symptoms of depression in urban areas of Indonesia. Education influences individual behavior, the higher the individual's education, the higher the level of knowledge through the ability to receive and rationalize information more easily. Our result might be used in developing the educational programs as a preventive and promotive effort by the government.